EGF is highly expressed in hepatocellular carcinoma (HCC) and promotes motility of HCC cells via fibronectin. Issue 5 (23rd January 2018) - Liu, Zongcai; Chen, Danyang; Ning, Fen; Du, Jun; Wang, Haifang
Abstract: Better understanding of metastasis process would allow for the development of effective approaches to treat hepatocellular carcinoma (HCC). Recent literature has highlighted the fundamental role of interaction between tumor cells and their microenvironment components in tumor metastasis. Aberrant expression of epidermal growth factor (EGF) induces highly malignant HCC, and activated EGF/EGFR signaling is correlated with an aggressive phenotype and intrahepatic metastasis. Thus, EGF in the tumor microenvironment may influence the behavior of HCC cells. In this study, for the first time, we studied the expression of EGF in HCCs, and the potential role of EGF in the motility of HCC cells and the underlying mechanisms. It was demonstrated that EGF was highly expressed in HCCs and positively associated with higher tumor grade. In addition, EGF promoted the migration and invasion of HCC cells mainly via induction of fibronectin (FN) in vitro. Mechanistically, EGF simultaneously increased the nuclear translocation and PKC mediated phosphorylation of p65 which could bind to the −356 bp to −259 bp fragment of FN promoter, leading to a markedly increased activity of FN promoter in HCC cells. These results highlight the potential role of EGF in promoting HCC metastasis, demonstrate a novel pathway for regulation of FN expression and provide potential targets for HCC prevention and treatment. Abstract : Epidermal growth factor (EGF) was highly expressed in hepatocellular carcinoma (HCCs), and positively associated with higher tumor grade. In vitro, EGF promoted the migration and invasion of HCC cells mainly via induction of fibronectin (FN).